2002
DOI: 10.1074/jbc.m207052200
|View full text |Cite
|
Sign up to set email alerts
|

Fragmin60 Encodes an Actin-binding Protein with a C2 Domain and Controls Actin Thr-203 Phosphorylation in PhysarumPlasmodia and Sclerotia

Abstract: We report the isolation of a cDNA clone encoding a 60-kDa protein termed fragmin60 that cross-reacts with fragmin antibodies. Unlike other gelsolin-related proteins, fragmin60 contains a unique N-terminal domain that shows similarity with C2 domains of aczonin, protein kinase C, and synaptotagmins. The fragmin60 C2 domain binds three calcium ions, one with nanomolar affinity and two with micromolar affinity. Actin binding by fragmin60 requires higher calcium concentrations than does binding of actin by a fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Capping of Actin Filaments-The experiments were performed essentially as described earlier (31,32). Briefly, preassembled unlabeled actin filaments (final concentration, 1 M) were used as "nuclei."…”
Section: Methodsmentioning
confidence: 99%
“…Capping of Actin Filaments-The experiments were performed essentially as described earlier (31,32). Briefly, preassembled unlabeled actin filaments (final concentration, 1 M) were used as "nuclei."…”
Section: Methodsmentioning
confidence: 99%
“…Gene knock-out experiments have implicated the actin severing properties of villin and gelsolin in their motogenic effect (5,6). However, all these proteins require very high calcium concentrations for actin severing (between 1 and 200 M) (7)(8)(9)(10)(11)(12)(13). Activation of gelsolin by Ca 2ϩ may be modulated by other factors as well (7,9,14).…”
mentioning
confidence: 99%
“…Physarum contains at least two other fragminlike molecules: amoebal fragmin (fragmin A; [Uyeda et al, 1988;T'Jampens et al, 1999]) and fragmin 60 [Furuhashi et al, 1992;Sklyarova et al, 2002]. The Physarum fragmin gene family is encoded by separate developmentally regulated genes; frgA is amoeba-specific [T'Jampens et al, 1999], whereas frgP and frg60 are plasmodium-specific [T'Jampens et al, 1997;Sklyarova et al, 2002]. The expression profile of afk is similar to those of frgP and frg60 [Sklyarova et al, 2002].…”
Section: Introductionmentioning
confidence: 91%
“…The Physarum fragmin gene family is encoded by separate developmentally regulated genes; frgA is amoeba-specific [T'Jampens et al, 1999], whereas frgP and frg60 are plasmodium-specific [T'Jampens et al, 1997;Sklyarova et al, 2002]. The expression profile of afk is similar to those of frgP and frg60 [Sklyarova et al, 2002]. Northern blot analysis showed that afk is not transcribed in amoeba.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation